Utilizing Second Hand Materials As Assisted Language Teaching Media For Madrasah Learners - Kasmaini Kasmaini (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2016)
The paper aimed at discussing the nurturing effects of utilizing second hand materials for encouraging English learning atmosphere among Madrasah learners. The paper was based on the community services program conducted by writer several months ago in collaboration with research and community services unit of IAIN Bengkulu. The program involved head master, English school teacher and 90 learners of Madrasah Tsanawiyah (MTs) Mambaul Ulum at central Bengkulu district. The usage of second hand materials is a great effort to achieve several goals among others; first, bringing the authentic materials into classroom teaching so the learners get closer to the materials given as they are found sorrounding their life. This approach may promote learners’ motivation and learning achievement. Second, encouraging teachers’ creativity in designing their own media without expense. Third, embedding the character education towards madrasah learners such as creativeness, cleanliness and prudent. The result showed that the classroom teaching was more active, and motivated in learning English and the teacher was more creative in designing the new authentic teaching media